Maternal child relationship and child development (Research, Society and Development, 2021)
Objective: To analyze the maternal and child bond of women assisted in a Basic Health Unit. Methodology: This is a descriptive, cross-sectional, exploratory study with a qualitative approach, carried out with 20 mothers of children up to 1 year old in the coverage area of the Family Health Unit Robson Cavalcante, located in Maceió / AL .The research was conducted through a semi-structured interview about the mother and baby bond and the data were processed through content analysis based on Laurence Bardin's proposal. Results: Maternal age ranged from 14 to 35 years, of which 6 were adolescents. The mothers' statements regarding changes through pregnancy predominantly involved the personal scope regarding maternal maturation. In general, on the importance of the bond, mothers find the relationship with the baby important for the construction of the child's personality and for recognition when they reach adulthood. Conclusion: Therefore, it is perceived that the stimuli that influence the child's growth and development are multifactorial, highlighting the planning of pregnancy, the maternal emotional and psychological state, the sensitivity of the mother, maternal overload, among others.